Peran Layanan Konseling Pusat Pembelajar Keluarga (PUSPAGA) Dalam Mencegah Kekerasan Anak Usia Dini - Latifah Isfuliah; Nasichah Nasichah; Kurnia Farhanah; Fivi Febrianti (Pusat Riset dan Inovasi Nasional, 2024)
The purpose of this study is to find out how the role of family learning center counseling services (PUSPAGA) in preventing early childhood violence. This research was motivated by the high problem of cases of violence in early childhood in Indonesia. The rise of cases of violence against children shows the need for effective protection and prevention efforts. PUSPAGA acts as the frontline in providing information, education, and counseling to prevent violence in early childhood. This study used the Library Research method with a literature review approach. Data collection techniques carried out are by reading, analyzing, and evaluating the results of existing research. The results of this study show that the factors causing an act of violence in children are economic factors and broken homes or divorce that can occur due to early marriage that causes parents not to have a mature emotional state in parenting. In the prevention of early childhood violence, PUSPAGA (Family Learning Center) will hold role playing classes, counseling programs for children and families, and premarital assistance for minors.